Art + DIY Electronics - Hertz, Garnet (The MIT Press, 2023)
A systematic theory of DIY electronic culture, drawn from a century of artists who have independently built creative technologies.Since the rise of Arduino and 3D printing in the mid-2000s, do-it-yourself approaches to the creative exploration of technology have surged in popularity. But the maker movement is not new: it is a historically significant practice in contemporary art and design. This book documents, tracks, and identifies a hundred years of innovative DIY technology practices, illustrating how the maker movement is a continuation of a long-standing creative electronic subculture. Through this comprehensive exploration, Garnet Hertz develops a theory and language of creative DIY electronics, drawing from diverse examples of contemporary art, including work from renowned electronic artists such as Nam June Paik and such art collectives as Survival Research Laboratories and the Barbie Liberation Organization. Hertz uncovers the defining elements of electronic DIY culture, which often works with limited resources to bring new life to obsolete objects while engaging in a critical dialogue with consumer capitalism. Whether hacking blackboxed technologies or deploying culture jamming techniques to critique commercial labor practices or gender norms, the artists have found creative ways to make personal and political statements through creative technologies. The wide range of innovative works and practices profiled in Art + DIY Electronics form a general framework for DIY culture and help inspire readers to get creative with their own adaptations, fabrications, and reimaginations of everyday technologies.